2022
DOI: 10.3389/fendo.2022.1059753
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram to predict the risk of peripheral artery disease in patients with type 2 diabetes mellitus

Abstract: ObjectiveTo develop and validate a nomogram for predicting the risk of peripheral artery disease (PAD) in patients with type 2 diabetes mellitus (T2DM) and assess its clinical application value.MethodsClinical data were retrospectively collected from 474 patients with T2DM at the Air Force Medical Center between January 2019 and April 2022. The patients were divided into training and validation sets using the random number table method in a ratio of 7:3. Multivariate logistic regression analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Therefore, prompt diagnosis and treatment of PVD in DM patients are crucial. Currently, PVD diagnosis primarily depends on imaging techniques like B-ultrasound and MRI ( 52 ). However, these methods can be costly and time-consuming, and with the rising number of diabetes cases, imaging every diabetic patient presents a considerable challenge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, prompt diagnosis and treatment of PVD in DM patients are crucial. Currently, PVD diagnosis primarily depends on imaging techniques like B-ultrasound and MRI ( 52 ). However, these methods can be costly and time-consuming, and with the rising number of diabetes cases, imaging every diabetic patient presents a considerable challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al. ( 52 ) developed a nomograph to predict the risk of PAD, however, nomograph method is inapplicable for large-scale datasets. Wilcox et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies corroborate a correlation between younger diabetes onset and augmented diabetic complications (31,32), positing elevated glycated hemoglobin levels and hastened pancreatic b-cell failure (33) as putative mechanisms, engendering formidable glycemic control challenges in this demographic. Blood urea nitrogen is extensively utilized in the assessment and prognosis of renal insufficiency and heart failure, therefore many previous studies have concentrated on the connection between BUN and diabetic nephropathy (34) or diabetic adverse cardiovascular events (35). In recent years, studies on the correlation between BUN and DR have shown a positive correlation, implying that DR, diabetic nephropathy, and severe cardiovascular events may all have a shared etiology linked to elevated blood urea nitrogen levels.…”
Section: Discussionmentioning
confidence: 99%